Development of a methodology for evaluating product service system as a competitive strategy for the Singapore manufacturing industry - Ang, Gim Ching Jenny (Cranfield University, 2010)
Product Service System (PSS) promotes the idea of selling value in use via an integrated combination of products and services. It has been regarded by many economic policy makers and researchers as a potential competitive strategy for the manufacturing industry in the developed country to gain competitiveness. Although currently there are a few PSS methodologies developed for the design and implementation of PSS, their approach is mainly biased towards using PSS as a tool to gain sustainability and to reduce environmental impact from selling more services instead of selling the physical product for example. In view of this, this research sets out to present a PSS Evaluation (PSSE) methodology, aiming at assisting manufacturer in assessing whether the adoption of a PSS is a good strategy from the point of competitiveness. The research programme begins with the identification of the requirements set of the PSSE methodology by gaining relevant knowledge from the literature and the Singapore‟s Manufacturing Industry. Existing potential methodologies were then selected against the requirements set to form the conceptual base of the new PSSE methodology. The developed new PSSE methodology was tested using two case studies during the primary evaluation and another four case studies during the secondary evaluation. The main contribution of this research is the development of a feasible, usable and useful methodology that can assist the manufacturer in assessing whether the adoption of a new PSS is a competitive strategy. The new seven-stage PSSE methodology provides well-constructed stages which are specially designed to be delivered via a facilitated workshop. This research has therefore made a significant contribution to the knowledge of the concept of PSS, and its application in the manufacturing industry in the area of methodology development.